COMPARING ORAL HEALTH HABITS AND DENTAL FLOSS USE AMONG MEDICAL AND DENTAL STUDENTS IN A PUBLIC UNIVERSITY IN PAKISTAN - Dr Aamir Hameed; Dr Aasim Masood; Dr Zaheer Baber; Dr Zia Ur Rehman Khalil; Dr Farah Shah; Dr Farah Shah; Dr Babar Ahad (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objectives: This study aimed to compare oral health habits, knowledge, and the frequency of dental floss use among undergraduate medical and dental students at a public university in Pakistan. Materials and Methods: A cross-sectional survey was carried out in Karachi Medical and Dental College for a period of three months on 200 medical and 200 dental students. Data were collected by administering a structured close-ended questionnaire self-completed by the respondents containing questions on oral hygiene practices and knowledge. Descriptive statistics were computed using Statistic Package for Social Sciences (SPSS) version 17; a p-value of < 0.05 was used as the level of significance. Results: The dental students brushed twice daily more often (76%) than the medical students (52%) and remained consistent in using dental floss (65% vs 28%). Medical students had a lower percentage of knowledge (68%) about the relationship between oral health and systemic diseases as compared to dental students (90%). Dental students also had significantly more frequent preventive dental visits than the general student population (70% vs. 40%). Conclusion: The findings also show that dental education brings changes in oral hygiene practices. Education of preventive oral healthcare should be incorporated in medical curricula for the better health behaviors of future health care professionals.